The Catalytic Activity of Modified Zeolite Lanthanum on the Catalytic Cracking of Al-Duara Atmospheric Distillation Residue. (Journal of Engineering, 2016)
Atmospheric residue fluid catalytic cracking was selected as a probe reaction to test the catalytic performance of modified NaY zeolites and prepared NaY zeolites. Modified NaY zeolites have been synthesized by simple ion exchange methods. Three samples of modified zeolite Y have been obtained by replacing the sodium ions in the original sample with lanthanum and the weight percent added are 0.28, 0.53, and 1.02 respectively. The effects of addition of lanthanum to zeolite Y in different weight percent on the cracking catalysts were investigated using an experimental laboratory plant scale of fluidized bed reactor.The experiments have been performed with weight hourly space velocity (WHSV) range of 6 to 24 h-1, and the range of temperature from 450 to 510 oC.The activity of the catalyst with 1.02 wt% lanthanum has been shown to be much greater than that of the sample parent NaY. Also it was observed that the addition of the lanthanum causes an increase in the thermal stability of the zeolite.